Full-Thickness Massive Rotator Cuff Repair With a Dermal Allograft Using CuffMend Augmentation Technique - Suhas P. Dasari BS; Luc M. Fortier BA; Blake M. Bodendorfer MD; Steven F. DeFroda MD, MEng; Brian J. Cole MD, MBA; Nikhil N. Verma MD (SAGE Publishing, 2022)
Background: Rotator cuff repair using graft augmentation for large-to-massive, full-thickness rotator cuff tears has been reported to have improved clinical outcomes relative to other therapeutic interventions. Although an effective and promising technique, graft augmentation can be technically challenging, particularly with deployment and positioning of the graft. CuffMend is a user-friendly rotator cuff augmentation technique that combines a decellularized dermal allograft with a novel graft deployment device, tendon anchor, and set of lateral knotless, tension-able anchors to allow for a reliable and stable implantation of the graft. Indications: Graft augmentation using CuffMend is indicated for tears with a high risk of retear or incomplete healing. This includes revision tears, poor-quality degenerative tissue, and massive full-thickness rotator cuff tears. Severe glenohumeral osteoarthritic change is the primary contraindication to this technique. Technique Description: The rotator cuff is reduced medially and secured using 3 anchors with sutures passed in a mattress configuration. Graft augmentation is then performed using the CuffMend graft spreader that facilitates placement and attachment of the graft onto the repaired tendon. Results: The patient is recovering as expected and started physical therapy 1 month postoperatively. He is able to perform light activities of daily living and reach the top of his head for daily self-care without pain. He will begin strengthening at 12 weeks postoperatively. Discussion/Conclusion: CuffMend is a new graft augmentation technique that uses a novel graft deployment device for consistent and precise deployment of a decellularized dermal allograft. This facilitates an expedited repair using the graft augmentation technique for optimal clinical and biomechanical outcomes in patients with rotator cuff tears with high risk of retear.